Requirement of Siderophore Biosynthesis for Plant Colonization by Salmonella enterica - Hao, Ling-yun (American Society for Microbiology, 2012)
Contaminated fresh produce has become the number one vector of nontyphoidal salmonellosis to humans. However, Salmonella enterica genes essential for the life cycle of the organism outside the mammalian host are for the most part unknown. Screening deletion mutants led to the discovery that an aroA mutant had a significant root colonization defect due to a failure to replicate. AroA is part of the chorismic acid biosynthesis pathway, a central metabolic node involved in aromatic amino acid and siderophore production. Addition of tryptophan or phenylalanine to alfalfa root exudates did not restore aroA mutant replication. However, addition of ferrous sulfate restored replication of the aroA mutant, as well as alfalfa colonization. Tryptophan and phenylalanine auxotrophs had minor plant colonization defects, suggesting that suboptimal concentrations of these amino acids in root exudates were not major limiting factors for Salmonella replication. An entB mutant defective in siderophore biosynthesis had colonization and growth defects similar to those of the aroA mutant, and the defective phenotype was complemented by the addition of ferrous sulfate. Biosynthetic genes of each Salmonella siderophore, enterobactin and salmochelin, were upregulated in alfalfa root exudates, yet only enterobactin was sufficient for plant survival and persistence. Similar results in lettuce leaves indicate that siderophore biosynthesis is a widespread or perhaps universal plant colonization fitness factor for Salmonella, unlike phytobacterial pathogens, such as Pseudomonas and Xanthomonas.